Firm Value Of The Agricultural Sector In Indonesia And Several Influencing Factors - Khairina Natsir; Nurainun Bangun; Riffulin Ni’matul Ishlah (Jurnal Manajemen, 2023)
During the Coronavirus-19 outbreak, from the six sectors that were able to achieve positive performance on the Indonesia Stock Exchange, the agricultural sector showed the highest increase of 3.770 per cent. The purpose of the study is to find academic proof about the influence of profitability, growth opportunity and business risk variables on the value of agricultural sector companies where capital structure functions as a mediating variable in the 2017 to 2021 period. With the purposive method obtained 24 samples of companies. The results of the study provide the proofs that profitability, business risk and capital structure have a positive effect on firm value. Growth opportunity has a negative effect on firm value, while profitability can have a positive effect on capital structure. Meanwhile, growth opportunity does not have a significant effect on capital structure, while business risk can affect capital structure. Another finding in this study is that capital structure is able to mediate profitability, growth opportunity, and business risk on firm value.